A dynamic kinetic asymmetric transfer hydrogenation–cyclization tandem reaction: an easy access to chiral 3, 4-dihydro-2H-pyran-carbonitriles. Issue 45 (22nd May 2017) - Zheng, Dongsong; Zhao, Qiankun; Hu, Xiaoying; Cheng, Tanyu; Liu, Guohua; Wang, Wei
Abstract : A catalytic enantioselective dynamic kinetic asymmetric transfer hydrogenation–cyclization tandem reaction is developed for 1, 3-difunctionalized racemic ketones. Abstract : A chiral (mesitylene)RuCl(monosulfonated diamine) catalysed dynamic kinetic resolution (DKR)–asymmetric transfer hydrogenation (ATH) process is developed for highly enantio- (up to 99% ee) and diastereo- (up to 98 : 2 dr) selective reduction of challenging racemic α-aryl-γ-keto malononitriles. A spontaneous cyclization reaction of the hydrogenation products delivers a cascade process for efficient synthesis of useful enantioenriched 3, 4-dihydro-2 H -pyran-carbonitriles.